2021
DOI: 10.1039/d1ob01543e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent styrylpyrylium probes for the imaging of mitochondria in live cells

Abstract: The first report of a family of styrylpyrylium dyes acting on mitochondria in a theranostic way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The skeleton structure of SM21 is pyrylium. As reported previously, fluorescent styrylpyrylium salts have been used for mitochondrial localization and visualization, indicating the mitochondria-targeting characteristics of pyrylium ( 27 ). In addition, a novel di-benzene-pyrylium-indolene was defined as an inhibitor of lipid II inhibitor, an essential component of bacterial cell wall synthesis, and showed effective activity against Enterococcus spp.…”
Section: Discussionmentioning
confidence: 76%
“…The skeleton structure of SM21 is pyrylium. As reported previously, fluorescent styrylpyrylium salts have been used for mitochondrial localization and visualization, indicating the mitochondria-targeting characteristics of pyrylium ( 27 ). In addition, a novel di-benzene-pyrylium-indolene was defined as an inhibitor of lipid II inhibitor, an essential component of bacterial cell wall synthesis, and showed effective activity against Enterococcus spp.…”
Section: Discussionmentioning
confidence: 76%
“…[5] The studies have revealed mitochondria to be the site of action of the pyrylium salts. [11] Pyridinium salts have been found to exhibit inhibitory effect on tumor-associated hCA IX and XII by promoting the synthesis of a variety of cytokines and chemokines, including TNF, interferon-a (IFN-a), interferon-g (IFN-g) and interferon-inducible protein-10 (IP-10). [12] Considering that Carbonic Anhydrase (CA1X and XII) is predominantly present in the cancer cells, pyridinium salts have been reported to inhibit Carbonic Anhydrase isoforms II and IV, suggesting the potential development of anti-cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that thiopyrylium dye inhibits proliferation of human colon carcinoma cell line CX1 [5] . The studies have revealed mitochondria to be the site of action of the pyrylium salts [11] . Pyridinium salts have been found to exhibit inhibitory effect on tumor‐associated hCA IX and XII by promoting the synthesis of a variety of cytokines and chemokines, including TNF, interferon‐a (IFN‐a), interferon‐g (IFN‐g) and interferon‐inducible protein‐10 (IP‐10) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…A new natural compound, tetrahydropyran containing galiumic acid, reveals antimicrobial activity [16]. Pyrylium salts are widely used as luminescent biolabels for imaging of proteins, nucleic acids, biogenic amines and surface amino groups [17][18][19]. Pyrylium derivatives allow improving mass spectrometry-based detection of peptides [20].…”
Section: Introductionmentioning
confidence: 99%